Case Report: A myxoma with a far reach - Akiki, Elias; Arghami, Arman; Abbasi, Muhannad A.; El-Am, Edward A.; Ahmad, Ali; Foley, Thomas A.; Daly, Richard C.; Maleszewski, Joseph J.; Kurmann, Reto; Klarich, Kyle W. (Frontiers in Cardiovascular Medicine, 2024)
A 73-year-old woman presented to the emergency department with a syncopal episode and a history of dizzy spells. A transthoracic echocardiogram demonstrated a large left atrial mass extending into the right upper pulmonary veins. Subsequently, cardiac magnetic resonance imaging and coronary computed tomography angiography with three-dimensional reconstruction and printing of the heart and mass were performed, which demonstrated a high index of suspicion for an atypical left atrial myxoma. The mass was excised robotically, and the pathology report confirmed a diagnosis of myxoma.